Fewer species of Argosarchus and Clitarchus stick insects (Phasmida, Phasmatinae): evidence from nuclear and mitochondrial DNA sequence data - Steven A. Trewick; Julia Goldberg; Mary Morgan‐Richards (Zoologica Scripta, 2005)
The systematics of three genera of New Zealand stick insect in the subfamily Phasmatinae were investigated in light of inconsistencies in morphological variability within and among species. We sequenced a region of the mitochondrial genome, cytochrome oxidase (COI & COII; 1448 bp), and a nuclear marker, the internal transcribed spacers (ITS1 & ITS2; 1804 bp) from 49 stick insects. Mitochondrial DNA sequence divergences among the three genera ( Argosarchus , Clitarchus and Acanthoxyla ) were relatively high (∼12%) but the current taxonomy within genera was not supported. Within the three genera, low levels of genetic divergence were observed at both nuclear and mitochondrial loci, and phylogenetic analyses failed to support reciprocal monophyly of the two species in Argosarchus and Clitarchus . Sympatric individuals of Argosarchus spiniger and A. horridus were more closely related to each other than to members of their respective morphospecies from elsewhere. No males were found in the Chatham Island population of Argosarchus and although this population has been referred to as A. schauinslandi , genetic and morphological evidence does not support its distinction from mainland Argosarchus . Likewise, individuals identified as Clitarchus tuberculatus were genetically identical, or most similar to, C. hookeri from the same or adjacent sites rather then grouping with the stick insects they were morphologically most similar to. Lack of spatial, behavioural or ecological evidence concordant with the described species A. spiniger , A. schauinslandi and C. tuberculatus leads us to infer that these species are synonymies of A. horridus and C. hookeri respectively. We conclude that Argosarchus and Clitarchus have each been over‐split and actually consist of a single morphologically polymorphic, facultative parthenogenetic species. The genus Acanthoxyla with eight described species also has low levels of genetic divergence, similar to those found in Argosarchus and Clitarchus . A possible hybrid origin of Acanthoxyla involving its sister genus Clitarchus is implied by sharing of ITS sequence variants, but further sampling is needed before the species status of these obligate parthenogenetic lineages can be resolved. In contrast to some New Zealand Orthoptera, the Phasmatinae show little genetic variation suggesting coalescence in recent times, possibly reflecting lineage sorting in the Pleistocene.